Scenario-Based Model for Aggregate Production Planning. Case Study in a Chemical Company - Mendoza, Gean Pablo; Vergara Rodríguez, Cesar Jose; Domínguez-Arrieta, Oscar Eduardo; Domínguez Canchila, Luz Mary (INGE CUC, 2021)
The objective of this research is to design a tool to support decision-making processes in medium-term production planning through a model for aggregate production planning, when demand is a parameter with uncertainty adjusted to a company that produces and distributes chemical products for cleaning, located in the municipality of Morroa - Sucre. The development of a production plan involves the determination of parameters that often have a certain degree of vagueness, this leads the personnel in charge of making decisions to assume the management of this uncertainty. This planning technique usually involves a family of similar products, i.e., products with similarities in the production process, the skills required, the materials needed. In this study the proposed model was coded in the General Algebraic Modeling System (GAMS) software, obtaining a solution in acceptable computational times. The solution obtained represents total production costs of $ 365'495,633 in the planning horizon, generating a planning tool for the company under study with favorable computational times.